Analytical Hierarchy Process (AHP) in Decision Support System for Assessing Service Performance of Puskesmas Muaro Jambi - Lidyawati, Indah; Astuti, Reny Wahyuning; Puspitorini, Sukma (Journal of Applied Business and Technology, 2024)
This research explores the use of the Analytic Hierarchy Process (AHP) as a decision-making tool for evaluating Pusat Kesehatan Masyarakat (Puskesmas) service performance. The study aims to demonstrate the effectiveness and usefulness of AHP in navigating complex decision-making processes. The AHP approach was employed to analyze collected data and assign priority levels and weights to various criteria, including health promotion, environmental health, maternal and child health (including family planning), nutrition improvement, disease prevention, treatment initiatives, and health development efforts. The system encompasses various data processing stages – from user and criteria data to value categories, sub-criteria, alternatives, and assessments. Ultimately, the system generated output in the form of ranking reports and visually presented final results. Among the Puskesmas services assessed, Puskesmas Tanjung emerged as the top performer, scoring a final value of 0.743389.